RELATIONSHIP BETWEEN CO-OPERATIVE SOCIETY GOVERNANCE - Ekhorutomwen, Asemota Abel; Peters, OJEALERO Benson (International Journal of Knowledge Content Development & Technology, 2021)
The study examines the relationship between co-operative society governance and members’ satisfaction. Co-operative societies face problems of how to keep balance between efficiency and governance because those in charge of operations of co-operative, the board and the staff must meet two demands; good business practice and the social responsibility which involves the satisfaction of members. The objective of this study is to examine the relationship between co-operative governance and members’ satisfaction using Ambrose Alli University Workers/Farmers Multi –Purpose Co-operative Society as a case study. The data collected in this study were obtained through structured questionnaire. Data analyzed were subjected to descriptive statistics. The data analyzed indicated that the challenges facing the co-operative society include theft /fraud and mismanagement; members we forced to agitate for transformation of the co-operative society to operate in line with the guidelines of the Central Bank of Nigeria. It was recommended that for efficiency and high productivity, staff should be trained. Also there is need for innovative technology and the necessity for cooperative society in question to network with other organizations.